Applying the WHO ICD-PM classification system to stillbirths in a major referral Centre in Northeast Nigeria: a retrospective analysis from 2010-2018 - Eseoghene Dase; Oghenebrume Wariri; Egwu Onuwabuchi; Jacob A. K. Alhassan; Iliya Jalo; Nazeem Muhajarine; Uduak Okomo; Aliyu U. ElNafaty (BMC Pregnancy and Childbirth, 2020)
Abstract Background Lack of a unified and comparable classification system to unravel the underlying causes of stillbirth hampers the development and implementation of targeted interventions to reduce the unacceptably high stillbirth rates (SBR) in sub-Saharan Africa. Our aim was to track the SBR and the predominant maternal and fetal causes of stillbirths using the WHO ICD-PM Classification system. Methods This was a retrospective observational study in a major referral centre in northeast Nigeria between 2010 and 2018. Specialist Obstetricians and Gynaecologists assigned causes of stillbirths after an extensive audit of available stillbirths’ records. Cause of death was assigned via consensus using the ICD-PM classification system. Results There were 21,462 births between 1 January 2010 and 31 December 2018 in our study setting; of these, 1177 culminated in stillbirths with a total hospital SBR of 55 per 1000 births (95% CI: 52, 58). There were two peaks of stillbirths in 2012 [62 per 1000 births (95% CI: 53, 71)], and 2015 [65 per 1000 births (95% CI, 55, 76)]. Antepartum and intrapartum stillbirths were almost equally prevalent (48% vs 52%). Maternal medical and surgical conditions (M4) were the commonest (69.3%) cause of antepartum stillbirths while complications of placenta, cord and membranes (M3) accounted for the majority (45.8%) of intrapartum stillbirths and the trends were similar between 2010 and 2018. Antepartum and intrapartum fetal causes of stillbirths were mainly due to prematurity which is a disorder of fetal growth (A5 and I6). Conclusions Most causes of stillbirths in our setting are due to preventable causes and the trends have remained unabated between 2010 and 2018. Progress toward global SBR targets are off-track, requiring more interventions to halt and reduce the high SBR.